MOSTRA VIRTUAL DE CIÊNCIAS COM CRIANÇAS: DESAFIOS DOS PROFESSORES FRENTE AO USO DAS TECNOLOGIAS DIGITAIS - Cavalheiro, Simone Teresinha Dias (2022)
This work is part of the research line "Teacher Training in Science and Mathematics Teaching" of the Graduate Program in Science and Mathematics Teaching (PPGECIMAT), Franciscan University (UFN). The importance of scientific education for children, since Early Childhood Education, is foreseen in the National Common Curriculum Base, and is one of the reasons that the Municipal School of Early Childhood Education Darcy Vargas (Santa Maria/ RS) used to hold a Science Show with children from 1 to 5 years, in the year 2020. Given the pandemic situation of COVID-19, which we have been living in since March 2020, this Exhibition had to be carried out virtually and remotely, with the use of digital technologies. However, many challenges have been overcome for the success of this work. Interested in continuing the Virtual Science Exhibition, the objective of this research work was to analyze the impact of digital technologies on teaching practice, during the 1st Virtual Science Exhibition, at the Darcy Vargas Municipal School of Early Childhood Education. The research had a qualitative, exploratory and descriptive approach. Data collection occurred through a questionnaire, answered by the teachers from nursery to preschool who participated in the Show; analysis of the Pedagogical Political Project (PPP) and other projects developed from the school, the Emergency Curriculum, used during remote teaching; and the work done at the Mostra. The results showed that the challenges presented were many: the teachers, for the most part, had little knowledge about digital resources and had to challenge themselves, to be available for new learning in order to be able to adapt to Remote Education; many difficulties in internet access (some students and parents without internet at home and without equipment for their access, others with low-speed internet access and via mobile technology). In addition, the lack of knowledge of the resources that would have to be used generated restlessness in teachers, because adequacy became necessary for all pedagogical activities to be carried out, as well as the Virtual Science Exhibition.